Patterns of Switching Behaviour of Ethnic Chinese Customers in Choosing Sharia Banking in Padang City - Hafnil Saputra; Helmalia Helmalia; Afrikal Candra; Lili Suarni; Nurlaila Nurlaila (Journal of Islamic Economics and Finance Studies, 2025)
Understanding customer switching behaviour patterns from conventional to Islamic banks forms the basis for analysing various motives or reasons. Essentially, the switching principle, whether in terms of savings, transactions, or investments, contributes to the emergence of the code of using Islamic banks as either a choice or in totality. This research is a phenomenological study with a descriptive qualitative analysis, which provides information on the direct pattern of customer switching behaviour. The study focuses on minority groups in the city of Padang, namely the Muslim and non-Muslim Chinese ethnic groups, who are predominantly entrepreneurs. The study results indicate that the switching behaviour of Chinese ethnic customers in Padang, who choose Islamic banks, is driven by various motives. Religious motives influence Muslim Chinese ethnicity due to fears about transactions prohibited by Islamic law, such as those containing ribawi elements. Other explanations include the need for Islamic banks, development and concern for Islamic banks, and commercial reasons like using cash flow transactions or inflows and outflows through interbank transfers using Islamic bank services, salary receipts, security, and service comfort. The final motive is the perception that Islamic bank products are more attractive and diverse. Non-Muslim Chinese ethnicity is influenced by security, especially from certain burdens, particularly on Wadi’ah Amanah savings products, which allow saving without incurring fees.